Pemanfaatan YouTube Sebagai Media Pembelajaran Maharah al-Istima’ di Madrasah Aliyah - Syahriramadhan, Muhammad; Faruq, Muh. (Prosiding Konferensi Nasional Bahasa Arab, 2023)
This research stems from the lack of development of Arabic language learning media in the madrasa environment and on the other hand, the existence of Arabic language textbooks published by the Ministry of Religious is not accompanied by supporting media for learning, especially listening skills. This research aims to develop digital learning media for YouTube-based listening learning. This research uses the Research and Development method with the ADDIE Model which focuses on three initial stages. At the analysis stage, it was found that there was a need for digital media for learning listening skills which was in line with the curriculum in textbooks published by the Ministry of Religion in 2020. At the design stage, the concept developed was video media equipped with interactive exercises using the YouTube as a base. and other platform as a supporting. YouTube was chosen because it has been accessed by many users easily. At the development stage, results were obtained in the form of YouTube-based learning videos in accordance with the curriculum in the Arabic textbook published by the Ministry of Religious.